Legal Aspects of Cyberwarfare and Cyberwarfare Crimes: Criminal Law Analysis and Dilemmas in the Legal System of the European Union - Šepec, Miha (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
The goal of this chapter is to analyse the substantive legal content regarding cyberwarfare attacks and crimes, present procedural measures of cooperation in criminal matters for the purpose of prosecuting such crimes, and examine European Union’s (EU) institutions for cooperation in such criminal matters. It should be emphasised that cyberwarfare does not have a single, clearly established legal definition. In most cases, cyberwarfare attacks refer to forms of cyberattacks that are already known, and which most EU Member States have already defined as criminal acts. The specifics of cyberwarfare are, thus, that it is connected with the army of an individual country, which then configures a military operation; and that the range and scope of the offence are significantly wider, as cyberwarfare attacks focuses on more important targets with significantly more repulsive motives, such as paralysing a country’s national security via attacks on its infrastructure and technological centres. The focus of the legal analysis is placed on the EU legislation and United Nations (UN) conventions, with particular interest on the legal definitions of terms connected to cyberwarfare (e.g. cyberattack, cyber espionage, and cyber-spying), understanding in which legal documents these terms are defined, and if these documents are legally binding to EU Member States. The study proves that cyberwarfare attacks are treated in the EU as crimes with a cross-border dimension of such nature and impact that they need special treatment, that is, they require a harmonising legislation at the EU level to prosecute such crimes more efficiently.Keywords: Cyberwarfare, Cyberattack, Defence Policy, Legal framework, Criminal Law, European Union